Drought and flood effects on macrobenthic communities in the estuary of Australia's largest river system. (5th November 2015) - Dittmann, Sabine; Baring, Ryan; Baggalley, Stephanie; Cantin, Agnes; Earl, Jason; Gannon, Ruan; Keuning, Justine; Mayo, Angela; Navong, Nathavong; Nelson, Matt; Noble, Warwick; Ramsdale, Tanith
Abstract: Estuaries are prone to drought and flood events, which can vary in frequency and intensity depending on water management and climate change. We investigated effects of two different drought and flow situations, including a four year long drought (referred to as Millennium drought) and a major flood event, on the macrobenthic community in the estuary and coastal lagoon of the Murray Mouth and Coorong, where freshwater inflows are strictly regulated. The analysis is based on ten years of annual monitoring of benthic communities and environmental conditions in sediment and water. The objectives were to identify changes in diversity, abundance, biomass and distribution, as well as community shifts and environmental drivers for the respective responses. The Millennium drought led to decreased taxonomic richness, abundance and biomass of macrobenthos as hypersaline conditions developed and water levels dropped. More taxa were found under very high salinities than predicted from the Remane diagram. When a flood event broke the Millennium drought, recovery took longer than from a shorter drought followed by small flows. A flow index was developed to assess the biological response subject to the duration of the preceding drought and flow volumes. The index showed higher taxonomic richness, abundance and biomass at intermediate and more continuous flow conditions. Abundance increased quickly after flows were restored, but the benthic community was initially composed of small bodied organisms and biomass increased only after several years once larger organisms became more abundant. Individual densities and constancy of distribution dropped during the drought for almost all macrobenthic taxa, but recoveries after the flood were taxon specific. Distinct benthic communities were detected over time before and after the drought and flood events, and spatially, as the benthic community in the hypersaline Coorong was split off with a salinity threshold of 64 identified by LINKTREE analysis. Salinity, low dissolved oxygen saturation and sediment properties accounted for further community splits in the estuarine Murray Mouth. This long term monitoring revealed ecological benefits of intermediate and continuous flow and that resilience of estuarine macrobenthos to drought and flood events was affected by flow history. The index can be applied to other flow regulated estuaries and inform environmental watering targets. Graphical abstract: Highlights: Resilience of estuarine benthos to droughts and floods was affected by flow history. FD index characterises freshwater inflow by volume, continuity and drought duration. Intermediate flow volumes and continuous flow beneficial for benthic communities. Long drought caused decrease of all benthic species, recoveries were species specific. Many species found over wide salinity range, communities distinct at salinities > 64.